Perceptions on Oral Corrective Feedback: The Case of Iranian EFL Teachers and Students in Face-to-Face and Virtual Learning Contexts - Sardabi, Narges; Ghajarieh, Amir; Atar Sharghi, Navid; Rahmani, Leyla (Journal of Teaching and Learning)

(untitled) (University of Windsor, 2025)
Oral-corrective feedback (CF) has often been a significant concern in Teaching English as a Foreign Language (TEFL). This study sought to investigate teachers’ and students' attitudes toward the oral CF in traditional and technology-enhanced classes. It also investigated the extent to which teachers' attitudes toward the oral CF matched their practices. A mixed-methods design was used for the study, utilizing data from questionnaires, observations, semi-structured interviews, and focus-group discussions. A sample of 162 female Iranian EFL students studying English at a private school participated in the study. The results showed that explicit correction (26%) and metalinguistic feedback (32%) were rated much more positively by the majority of students. Furthermore, the results indicated that they were more accustomed to receiving oral-feedback from the teacher in face-to-face classes than text- or audio-based feedback in technology-enhanced lessons. In addition, teachers' attitudes toward the CF were categorized into four themes: students' affective responses to CF, reasons for providing CF, timing of CF, CF in face-to-face instruction, and technology-enhanced instruction. The findings also showed that teachers' expressed beliefs about the frequency of CF provision predicted their practices, in many cases. This research has implications for EFL teachers and materials developers.